Synthesis, characterization, and electrochemical and electrical properties of a novel ball-type hexanuclear metallophthalocyanine, bridged by calix[4]arenes substituted with four hexylthiometallophthalocyanines through nitro coupling - (:unkn) unknown (WORLD SCI PUBL CO INC, 2007)
In this study, the synthesis of a supramolecular hexaphthalocyaninato hexazinc(II) with hexylthio substituents is reported. Starting from 5,11,17,23-tetra-tert-butyl-25,27-dihydroxy-26,28 -dimethoxycalix[4]arene, mononitro derivative of calix[4]arene 1 was obtained. Compound 1 was converted to phthalodinitrile derivative 2 by the reaction with 4-nitrophthalonitrile in dry dimethylsulfoxide by the method of nucleophilic substitution of an activated nitro group in an aromatic ring. The tetramerization of compound 2 with Zn(OAc)(2)center dot 2H(2)O in 1-pentanol gave the novel ball-type binuclear zinc (11) phthalocyanine 3 which was reacted with unsymmetric zinc(II) phthalocyanine 4 to furnish a supramolecular assembly of a zinc(II) phthalocyanine of a ball type with four zinc(II) phthalocyanines through azo bridges, 5. Newly synthesized compounds were characterized by elemental analysis, UV-vis, IR, MALDI-TOF MS and H-1 NMR spectra. The electrochemical and spectroelectrochemical properties of 5 were also examined in nonaqueous media. The measurements showed the formation of various mixed-valence oxidation and reduction species, due to the strong intramolecular interactions between the Pc rings. Both DC and AC conductivity data were analyzed by the existing theory. Copyright (C) 2007 Society of Porphyrins & Phthalocyanines.
Keywords: phthalocyanine; calixarene; ipso-aromatic nitration; conductivity; electrochemistry; spectroelectrochemistry.; GAS-SENSING PROPERTIES; METAL-FREE; PHTHALOCYANINES; SPECTROSCOPY; 1,2-BIS(3,4-DICYANOPHENOXYMETHYL)BENZENE; CLAMSHELL; COMPLEXES; TRIAZINE; ZINC(II)